Revisiting transthyretin related cardiac amyloidosis: Case report and review of literature - Sharma, Munish (Clin Pract, 2018)
Amyloidosis is a complex group of disorders that can involve many organs and cause their dysfunction. Cardiac involvement indicates worse prognosis and influences treatment strategies. Cardiac amyloidosis is an under-diagnosed entity and high index of clinical suspicion and careful interpretation of basic diagnostic tools such as electrocardiogram and echocardiography is needed for early detection. Congestive heart failure due to restrictive pattern and/or conduction system abnormality, in absence of coronary artery disease should raise suspicion. We present a case of transthyretin related cardiac amyloidosis and discuss the key clinical and diagnostic findings along with review of existing literature regarding its management and outcomes.